Mediastilʹ i ego intenconalʹno-narrativnaâ struktura - Klušina, Natalʹâ I. (Stylistyka, 2019)
In this article Mediastylistics as an independent scientific discipline which is a part of medialogia and stylistics is discussed. Integrative category of style is a basis forstylistics. Integrative category of mediastyle is a basis for mediastylistics. Mediastyle is more widely used than publicistic style which has been researched by functional stylistics. We are researching mediastyle by dividing the concepts of style and discourse. Mediastyle has an unique intentional and narrative structure. Intentionality of mediastyle shows its unique, narrative structure – its national content.